Plumeria obtusa Leaf Powder Supplemented in the Diet of Pekin Ducks: Effect on Growth Performance, Carcass Characteristics and Caecal Microflora Count - Olujimi, Alagbe John (PT. Riset Press International, 2025)
This experiment was carried out to evaluate Plumeria obtusa leaf powder supplemented in the diet of Pekin ducks: effect on growth performance, carcass characteristics and caecal microflora count. 400 Pekin ducklings (mixed sex) were used in the 42 days trial (Poultry Unit of Sumitra Research Institute, India) with an initial body weight of 42.55± 1.35 g were randomly distributed into five treatment groups with ten replicates (10 birds per replicate). An experimental bird (basal diet) was compounded following the requirement for ducks according Nutritional Research Council’s recommendation in 1994. Ducks in group A which also served as the control, was fed basal diet only, group B received basal diet supplemented with Oxytet® Plus (synthetic antibiotics) at 0.25 g/kg diet while those in group C, D and E were fed same diet (basal diet) supplemented with Plumeria obtusa leaf powder at 20 g, 40 g and 60 g/kg diet respectively. Average daily weight gain and average daily feed intake were higher in birds fed Plumeria obtusa leaf powder (C, D and E), intermediate in group B and lowest in group A (p˂0.05). Feed to gain ratio decreased as the level of Plumeria obtusa leaf powder increased in the diet (p˂0.05). Dressed percentage, eviscerated weight were significantly (p˂0.05) influenced by the diet except for the relative weights of heart, liver, spleen, head, back, thigh, drumstick, breast and wing (p˃0.05). Escherichia coli, Pseudomonas spp, Staphyllococcus spp and Stereptococcus spp counts were higher in group A relative to the other treatments. Conversely, Lactobacillus spp count were higher in group C, D and E compared to the other groups. It was concluded that dietary supplementation of Plumeria obtusa leaf powder up to 60 g/kg had to negative effect on the performance of ducks.